Effect of electron irradiation on structural, morphological and photoluminescence properties of ZnS thin films. Issue 8 (June 2016) - Dhaygude, H.D.; Shinde, S.K.; Takale, M.V.; Lohar, G.M.; Rath, M.C.; Fulari, V.J.
Abstract: Here, we present the effect of electron irradiation on the structural, morphological and optical properties of ZnS thin films. In brief, ZnS thin films have been synthesized by an electrodeposition method. ZnS thin films are further characterized by different techniques such as X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), band gap, contact angle, photoluminescence etc. XRD shows enlargement of well crystallized films with pure-hexagonal phase of ZnS thin films in both pre-irradiation and post-irradiation. All sample ZnS thin films show superior optical properties with high transmittance in the visible region and the band gap value decreases from 3.10–1.70 eV after irradiation. Surface wettability with solid–liquid interface showed hydrophilic nature after irradiation. Graphical abstract: Fig. Contact angle with different irradiation doses.